Lucilia sericata strain from Colombia: Experimental Colonization, Life Tables and Evaluation of Two Artificial Diets of the Blowfly Lucilia sericata (Meigen) (Diptera: Calliphoridae), Bogota, Colombia Strain (2010)
The objective of this work was to establish, under experimental laboratory conditions, a colony of Lucilia sericata, Bogota-Colombia strain, to build life tables and evaluate two artificial diets. This blowfly is frequently used in postmortem interval studies and in injury treatment. The parental adult insects collected in Bogota were maintained in cages at 22 degrees C +/- 1 average temperature, 60%+/- 5 relative humidity and 12 h photoperiodicity. The blowflies were fed on two artificial diets that were evaluated over seven continuous generations. Reproductive and population parameters were assessed. The life cycle of the species was expressed in the number of days of the different stages: egg = 0.8 +/- 0.1, larvae I = 1.1 +/- 0.02, larvae II = 1.94 +/- 0.16, larvae III = 3.5 +/- 1.54, pupae = 6.55 +/- 0.47, male adult = 28.7 +/- 0.83 and female adult = 33.5 +/- 1.0. Total survival from egg stage to adult stage was 91.2% for diet 1, while for diet 2 this parameter was 40.5%. The lifetime reproductive output was 184.51 +/- 11.2 eggs per female. The population parameters, as well as the reproductive output of the blowflies that were assessed, showed relatively high values, giving evidence of the continuous increase of the strain over the different generations and making possible its maintenance as a stable colony that has lasted for more than two years.